2021
DOI: 10.3390/vaccines9090940
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and Perceptions of the Arabic-Speaking Community in Sydney, Australia, toward the Human Papillomavirus (HPV) Vaccination Program: A Qualitative Study

Abstract: Background: Little is known about acceptability of the human papillomavirus (HPV) vaccine among parents of adolescents from culturally and linguistically diverse backgrounds in Australia. This study aimed to explore the knowledge and attitudes of parents from Arabic backgrounds towards HPV vaccination offered to their children in the national school-based vaccination program. Methods: Qualitative interviews were conducted in Western Sydney, with parents of adolescents from Arabic backgrounds. Recruitment was v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…Mothers felt that language discordance was a barrier to HPV/HPVV communication with the provider, including the possibility that the message was lost when a child interpreted the encounter. Similar issues were detected among Arab immigrant parents in Australia [ 28 ]. Providers need Arabic language educational materials to distribute to Arabic-speaking parents and ready access to professional medical interpretation services.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…Mothers felt that language discordance was a barrier to HPV/HPVV communication with the provider, including the possibility that the message was lost when a child interpreted the encounter. Similar issues were detected among Arab immigrant parents in Australia [ 28 ]. Providers need Arabic language educational materials to distribute to Arabic-speaking parents and ready access to professional medical interpretation services.…”
Section: Discussionsupporting
confidence: 69%
“…Recent MENA studies have found women’s HPVV knowledge and awareness to be “poor” [ 26 , 27 ]. In a qualitative study among Arab, mostly immigrant, parents of vaccine-eligible children in Sydney, Australia, not having enough information to make a decision was also an HPVV barrier [ 28 ]. Our findings suggest that, although the HPVV has been approved for over fifteen years, information about it has not been disseminated sufficiently through the NYC Arab immigrant parent population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to an advisory committee in June 2019, the HPV vaccination may be given to persons aged 27 to 45 years. This advice is based not just on safety and effectiveness, but rather on vaccination effectiveness and cost-efficiency [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%